THE CURRENT SITUATION OF COMMUNITY INTEGRATION FOR SCHIZOPHRENIA PATIENTS AT DONG DA WARD HEALTH STATION, HANOI CITY (Vietnam Journal of Community Medicine, 2026)
Objective: Describes of the current state of community integration measured by the Community Integration Questionnaire-Revised scale (CIQ–R) and related factors among patients with schizophrenia at Dong Da Ward Health Station, Hanoi City 2025.Subject and method: This is a cross-sectional descriptive study 94 patients with schizophrenia among the age of 18-65 with duration of illness at least 1 year who received outpatient treatment from October 2025 to March 2026.Results: The median age was 53 ± 14, and the duration of illness was 27,50 ± 16,25 years. The majority were male (75,5%), unemployed (83,0%), and had low incomes (64,9%). Community integration (CIE) was low (7,70 ± 5,72). Females scored higher than males in the family integration, social integration, and overall scores, with statistical significance (p < 0.05). The older the age and longer the duration of illness, the lower the CIE. Those with incomes > 750,000 VND/month and who were employment had higher CIE. No association was found between CIE and educational level, medication adherence, and family function (p > 0.05).Conclusion: In addition to managing and supporting patients’ adherence to medication treatment, relevant agencies and the healthcare system need to work together towards models of social rehabilitation and vocational support to improve the quality of life for patients with intellectual disabilities and reduce the overall burden on society.
Keywords: Community integration, schizophrenia, medication adherence, family support.